2018
DOI: 10.1371/journal.pone.0209121
|View full text |Cite
|
Sign up to set email alerts
|

Grit is associated with lower level of depression and anxiety among university students in Chiang Mai, Thailand: A cross-sectional study

Abstract: BackgroundDepression and anxiety symptoms are prevalent among university students in both developed and developing settings. Recently, grit, defined as perseverance and passion for longterm goals, has emerged as an indicator of success and well-being. However, the relationship between grit and poor mental health outcomes among university students is largely unknown. The current study investigates the relationship of grit with depression and anxiety among university students in Chiang Mai, Thailand. MethodsThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
87
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 40 publications
10
87
0
1
Order By: Relevance
“…In the general population, the prevalence of mood and anxiety disorders in East-Asian countries is lower than that in Western countries [25,26]. In Asian medical students, the prevalence of depression varies broadly, being 10.3% in Korea [27], 21.4% in Thailand [28], and 29% in China [29]. There are a few studies on the prevalence of depression in Japanese medical students.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, the prevalence of mood and anxiety disorders in East-Asian countries is lower than that in Western countries [25,26]. In Asian medical students, the prevalence of depression varies broadly, being 10.3% in Korea [27], 21.4% in Thailand [28], and 29% in China [29]. There are a few studies on the prevalence of depression in Japanese medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that grit was associated with general well-being (Salles et al, 2014;Datu et al, 2016;Kleiman et al, 2013;Hill et al, 2016;Musumari et al, 2018), but little research had been conducted to investigate the link between grit and lifestyle. Our results showed that grit was negatively and directly correlated with lifestyle score (β = -13.712, p < .001), i.e., students with higher levels of grit led significantly healthier lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…Grit has been correlated with student retention (Saunders-Scott, Braley, & Stennes-Spidahl, 2018), but perseverance was found to be most useful for predicting success (Crede, Tynan, & Harms, 2017). Grit is also associated with various well-being outcomes, such as, psychological well-being (Salles, Cohen, & Mueller, 2014), behavioral engagement, emotional engagement, flourishing (Datu, Valdez, & King, 2016), enhanced purpose in life (Kleiman, Adams, Kashdan, & Riskind, 2013;Hill, Burrow, & Bronk, 2016), and lower levels of depression and anxiety (Musumari et al, 2018). Grit may be particularly useful for those who have resolved their identities and identified with their commitments (Weisskirch, 2019).…”
mentioning
confidence: 99%
“…Moreover, our study uniquely found that NCS were associated with lifestyle as characterized by homework submission This study was also the first to examine adolescent mental health in the context of NCS. While previous research has examined mental health among university students in relation to the NCS [29,30], adolescents had not yet been considered. In addition, research has indicated that grit and school satisfaction are positively associated among adolescents [12], but few studies have examined how these items relate to mental health.…”
Section: Discussionmentioning
confidence: 99%